Dry film resist

The dry film resist composition with resol-modified xylene formaldehyde resin and quinonediazide sulfonic acid ester addresses adhesion and reproducibility issues in positive dry film resists, ensuring effective lamination and pattern integrity in high-speed processes.

JP2025012688APending Publication Date: 2025-01-24MITSUBISHI PAPER MILLS LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023115718
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing positive dry film resists face issues with poor adhesion to base materials during thermocompression bonding, leading to reduced resist pattern reproducibility and increased sensitivity changes over time, especially in roll-to-roll processes.

Method used

A dry film resist composition comprising a support film with a release layer and a positive photosensitive resist layer containing resol-modified xylene formaldehyde resin and quinonediazide sulfonic acid ester, which improves adhesion and reduces the top width of resist patterns by minimizing elution during development.

Benefits of technology

The solution enhances lamination properties and resist pattern reproducibility by maintaining adhesion to the base material, reducing the top width of resist patterns, and minimizing sensitivity changes over time, suitable for high-speed thermocompression bonding processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012688000001
    Figure 2025012688000001
  • Figure 2025012688000002
    Figure 2025012688000002
  • Figure 2025012688000003
    Figure 2025012688000003
Patent Text Reader

Abstract

To provide a positive type dry film resist which is excellent in laminate property to a base material, and improves lowering of resist pattern reproduction property that is caused by elution of a non-exposed part by a developer and is accompanied by reduction in a top width of the resist pattern, when a photosensitive resist layer is exposed and developed and a pattern is formed.SOLUTION: A dry film resist has a support film (A), and a positive photosensitive resist layer (C) containing a resol-modified xylene-formaldehyde resin (b) containing at least a specific constitutional unit (I) and a specific constitutional unit (II), and a quinone diazidosulfonate ester (c), on the support film (A), wherein the quinone diazidosulfonate ester (c) is a polycondensate of phenol formaldehyde and sulfonate of o-naphthoquinone diazide, or a polycondensate of alkylphenol formaldehyde and sulfonate of o-naphthoquinone diazide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dry film resist. [Background technology]

[0002] For example, a method of etching metals of various substrates is known in the manufacture of metal masks, lead frames, shadow masks, printed circuit boards, etc. As the resist used in this etching, a photosensitive resin composition utilizing photocrosslinking by mixing a water-soluble polymer compound such as polyvinyl alcohol (PVA), gelatin, casein, etc. with a photocrosslinking reagent such as ammonium dichromate has been used. However, this photosensitive resin composition has problems such as the difficulty of treating chromium waste liquid, and at present, most of them have been replaced by dry film resists using an alkaline aqueous solution developing type photosensitive resin composition.

[0003] Currently, negative photosensitive resists are used as dry film resists, and a composition that combines an alkali-soluble resin, a photopolymerizable crosslinking agent, and a photopolymerization initiator is generally used. A dry film resist using a negative photosensitive resist is thermocompressed onto a substrate to form a photosensitive resist layer, and the photosensitive resist layer is cured and made insoluble in an image-like manner by exposure to ultraviolet light through a photomask on which an image is formed. The unexposed areas are then dissolved into an alkaline developer, typically a 1% by mass aqueous solution of sodium carbonate, to form a resist pattern. Then, an etching process is performed using the resist pattern as a mask pattern.

[0004] However, negative photosensitive resists have problems such as changes in the sensitivity of the composition over time and the generation of residues of resist components on the surface of the substrate after development. In addition, when removing the resist after metal etching, it is necessary to use a special remover solution that is strongly alkaline or contains an organic amine.

[0005] On the other hand, positive-type photosensitive resists have the advantage that the photosensitive resist layer in the exposed areas is removed, so it is less susceptible to the effects of oxygen in the air that inhibits photopolymerization, there is little change in sensitivity over time, and the resist pattern can be easily dissolved and peeled off by exposing the entire surface of the resist to light and treating it with a developer after etching the substrate. Also, compared to negative-type photosensitive resists, the resist layer is less likely to swell in a developer, which is advantageous for forming fine patterns.

[0006] Positive photosensitive resists are widely used in the form of liquid resists, which are applied directly to a substrate by spin coating, roll coating or the like. However, in recent years, due to their simplicity, there has been a strong demand for a method in which a positive photosensitive resist is made into a dry film resist and laminated to a substrate by thermocompression bonding.

[0007] Positive photosensitive resists that have been widely used in the past include materials mainly composed of quinone diazide compounds and novolac resins (for example, Patent Document 1). However, in positive dry film resists mainly composed of quinone diazide compounds and novolac resins, the rigidity and Tg of the positive photosensitive resist layer are high, and there is a problem that poor adhesion to the substrate is likely to occur during thermocompression bonding. If poor adhesion occurs during thermocompression bonding, the resist cannot be used as an etching resist, so as described in Patent Document 5 below, there is a disclosure that the molecular weight of the co-condensed novolac resin is reduced to reduce the Tg of the positive photosensitive resist layer and improve flexibility. However, even when a low-molecular-weight co-condensed novolac resin is used, poor adhesion is likely to occur due to the high softening point resulting from the rigidity of the novolac resin structure, especially when applying thermocompression bonding in a roll-to-roll process, unless the operation is performed at a very low speed. From the viewpoint of productivity, there is a demand for a positive dry film resist that maintains the reproducibility of fine resist patterns and has excellent lamination properties to substrates without requiring low-speed operation during thermocompression bonding.

[0008] Patent Document 2 discloses an aromatic hydrocarbon formaldehyde resin, which is a condensation reaction product between an aromatic hydrocarbon having a substituted or unsubstituted benzene ring and formaldehyde, and its modified product as a film-forming composition for lithography that can be used for both negative and positive types. By using this film-forming composition, which has a structure more flexible than novolac resin, in a dry film, it is possible to improve the flexibility of the positive photosensitive resist layer and the adhesion to the substrate by thermocompression bonding. However, this document shows an example of its use as a thin liquid resist, and there are many insufficient points in terms of film-forming property on a support and developability to simply convert it into a dry film.

[0009] Patent Documents 3 to 5 exemplify a method of achieving both the resolution of a positive photosensitive resist layer and the flexibility of a coating film as a dry film by using a phenolic resin having an aralkyl group such as a xylylene unit or biphenyl in combination with a novolac resin. However, in this technology, the phenolic resin having an aralkyl group has low compatibility in the coating liquid that forms the coating film due to the high localization of the hydrophobic unit in the molecule, and unevenness or whitening may occur in the positive photosensitive resist layer.

[0010] In response to these problems, the applicant of the present application has filed a patent application for a positive dry film resist that uses a resol-modified xylene formaldehyde resin, which has high stability of the coating liquid and liquid film and can be laminated by thermocompression bonding (Patent Document 6). However, since the resol-modified xylene formaldehyde resin has a lower ratio of phenolic hydroxyl groups compared to ordinary phenol resins, the effect of inhibiting dissolution in an alkaline developer by the quinone diazide ester compound tends to be insufficient, and even unexposed areas are partially dissolved during development, and the top width of the resist pattern near the apex of the resist pattern is reduced more than when ordinary phenol resins are used, which may result in a decrease in reproducibility of the resist pattern, and further improvement is required. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2006-267660 A [Patent Document 2] International Publication No. 2019 / 098338 [Patent Document 3] JP 2020-98241 A [Patent Document 4] JP 2020-98242 A [Patent Document 5] JP 2020-98244 A [Patent Document 6] Patent application No. 2023-093321 Summary of the Invention [Problem to be solved by the invention]

[0012] An object of the present invention is to provide a positive dry film resist which has excellent lamination properties to a substrate and which improves the decrease in resist pattern reproducibility associated with a decrease in the top width of the resist pattern, which is caused by the elution of unexposed areas by a developer, when a photosensitive resist layer is exposed and developed to form a pattern. [Means for solving the problem]

[0013] The above-mentioned problems are solved by the following invention.

[0014] A dry film resist comprising: a support film (A); and a positive photosensitive resist layer (C) on the support film (A), the positive photosensitive resist layer (C) containing a resol-modified xylene formaldehyde resin (b) containing at least a structural unit (I) represented by the following general formula (1) and a structural unit (II) represented by the following general formula (2), and a quinone diazide sulfonic acid ester (c), the quinone diazide sulfonic acid ester (c) being a polycondensate of a sulfonic acid ester of phenol formaldehyde and o-naphthoquinone diazide, or a polycondensate of a sulfonic acid ester of an alkylphenol formaldehyde and o-naphthoquinone diazide.

[0015] [ka]

[0016] [ka]

[0017] (In general formulas (1) and (2), X each independently represents -CH2- or -CH2-O-CH2-, and in general formula (2), m represents an integer of 1 to 2, and when the resin (b) contains a plurality of structural units (II), m in each structural unit (II) may be the same or different.) Effect of the Invention

[0018] According to the present invention, it is possible to provide a positive dry film resist which has excellent lamination properties to substrates and which improves the decrease in resist pattern reproducibility associated with a decrease in the top width of the resist pattern, which is caused by the elution of unexposed areas by a developer, when a photosensitive resist layer is exposed and developed to form a pattern. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will be described in detail below. The dry film resist of the present invention comprises a support film (A) and a positive photosensitive resist layer (C) on the support film (A), the positive photosensitive resist layer (C) containing a resol-modified xylene formaldehyde resin (b) containing at least a structural unit (I) represented by the following general formula (1) and a structural unit (II) represented by the following general formula (2), and a quinone diazide sulfonic acid ester (c).

[0020] <Support film (A)> The support film (A) is not particularly limited. The support film (A) may be a transparent film that transmits light, or a white or colored film that blocks light. Examples of such support films include polyolefins such as polypropylene and polyethylene; polyimides; polyester films such as polyethylene naphthalate, polyethylene terephthalate, and flame-retardant polyethylene terephthalate; and films such as polycarbonate, polyphenylene sulfide, polyetherimide, modified polyphenylene ether, and polyurethane. Among these, the use of a polyethylene terephthalate film is particularly advantageous in terms of lamination suitability, peelability, and smoothness, and is also very easy to use due to its advantages of being inexpensive, not brittle, having excellent solvent resistance, and having high tensile strength.

[0021] The thickness of the support film (A) is preferably from 1 to 100 μm, and more preferably from 12 to 50 μm.

[0022] <Peeling layer (B)> In the dry film resist of the present invention, the support film (A) preferably has a release layer (B) on the surface having the positive photosensitive resist layer (C). By having the release layer on the support film (A), the support film (A) and the release layer (B) can be simultaneously and easily peeled off from the positive photosensitive resist layer (C).

[0023] When the support film (A) has a release layer (B), the release layer (B) is preferably a layer containing polyvinyl alcohol. The release layer (B) can be formed, for example, by applying a coating liquid for release layer containing polyvinyl alcohol onto the support film (A).

[0024] When the support film (A) has a release layer (B), the release layer (B) side of the support film (A) may be subjected to a corona discharge treatment. The corona discharge treatment can be performed by irradiating the surface of the support film (A) with a corona discharge from an electrode. By subjecting the surface of the support film (A) to a corona discharge treatment, the adhesion between the support film (A) and the release layer (B) can be increased, making it easier to simultaneously peel off the support film (A) and the release layer (B) from the positive photosensitive resist layer (C). The preferred corona discharge amount is 10 to 200 W·min / m 2 It is.

[0025] Furthermore, when the support film (A) has a release layer (B), the positive photosensitive resist layer (C) can be formed uniformly without unevenness on the release layer (B). The polyvinyl alcohol contained in the release layer (B) is preferably polyvinyl alcohol having a saponification degree of 82 mol% or more, more preferably 82 to 99.5 mol%, and even more preferably 83 to 98 mol%. The polyvinyl alcohol used may be unmodified or may be partially modified with a modified group to impart functionality such as water resistance, solvent resistance, heat resistance, barrier properties, and flexibility. Synthetic products or commercially available products may be used.

[0026] Commercially available polyvinyl alcohol products include, but are not limited to, Kuraray Poval (registered trademark) 3-98, 4-98 HV, 5-98, 11-98, 28-98, 60-98 (all having a degree of saponification of 98 to 99 mol%), 3-88, 5-88, 9-88, 22-88, 30-88, 44-88, 95-88 (all having a degree of saponification of 86 to 89 mol%), 29-99, 25-100 (all having a degree of saponification of 99 mol%), manufactured by Kuraray Co., Ltd.; JC-25, JC-33 (all having a degree of saponification of 99 mol%), JF-03, JF-04, JF-05 (all having a degree of saponification of 98 to 99 mol%), JP-03, JP-04 (all having a degree of saponification of 86 90 mol%), JP-05 (degree of saponification = 87 to 89 mol%), JP-45 (degree of saponification = 86.5 to 89.5 mol%), JL-18E (degree of saponification = 83 to 86 mol%), and Mitsubishi Chemical Corporation's Gohsenx (registered trademark) series Z-100, Z-200, Z-205 (degree of saponification = 99 mol% or more), Z-300, Z-410 (degree of saponification = 97.5 to 99 mol%), Z-210 (degree of saponification = 95 to 97 mol%), Z-220, Z-320 (degree of saponification = 90.5 to 94 mol%).

[0027] In the release layer (B), the content of polyvinyl alcohol is preferably 80 to 100% by mass, more preferably 90 to 100% by mass, and even more preferably 95 to 100% by mass, based on the total solid content of the release layer (B). If the content is less than 80% by mass, it may be difficult to adjust the adhesion between the release layer (B) and the positive photosensitive resist layer (C), and the adhesion may be too high, making it difficult to peel off the release layer (B) and the support film (A) together. When the support film (A) is peeled off, the release layer (B) may remain on the positive photosensitive resist (C), or the positive photosensitive resist layer (C) may be partially peeled off, and the adhesion between the release layer (B) and the positive photosensitive resist layer (C) may decrease, and the positive photosensitive resist layer (C) may easily crack or peel off when the film is folded.

[0028] When the content of polyvinyl alcohol in the release layer (B) is less than 100% by mass, the remaining components include low molecular weight compounds such as plasticizers, high molecular weight compounds, etc. Examples of these compounds include water-soluble resins such as polyethylene glycol, polypropylene glycol, poly(meth)acrylic acid, poly(meth)acrylic acid esters, carboxymethylcellulose (CMC), glue, casein, sodium alginate, vinyl acetate resin, polyvinylpyrrolidone, and polyacryloylmorpholine.

[0029] In the release layer (B), the content of polyvinyl alcohol having a saponification degree of 82 mol% or more is preferably 80 to 100 mass%, more preferably 90 to 100 mass%, and even more preferably 95 to 100 mass% based on the total solid content of the release layer (B). When the content is less than 80 mass%, the adhesion between the release layer (B) and the positive photosensitive resist layer (C) becomes too high, which may make it difficult to peel off the release layer (B) and the support film (A) together, and when peeling off the support film (A), the release layer (B) may remain on the positive photosensitive resist (C), or may be partially peeled off together with the positive photosensitive resist layer (C). When the content is less than 100 mass%, the remaining components are not particularly limited, but may include low molecular weight compounds such as plasticizers or polymer compounds as described above. In addition, polyvinyl alcohol having a saponification degree of less than 82 mol% may be used.

[0030] The thickness of the release layer (B) is preferably 1 μm or more, more preferably 2 μm or more. Also, it is preferably 20 μm or less, more preferably 10 μm or less. If it is thinner than 1 μm, problems of thickness unevenness and pinholes may easily occur when a film is formed. If it is thicker than 20 μm, the coating liquid for the release layer is difficult to dry, and the drying process after coating tends to be prolonged. Also, in order to solve the problem of pinhole defects caused by air bubbles remaining in the coating liquid for the release layer, it is more preferable that the thickness of the release layer (B) is 4 μm or less. The thickness of the release layer (B) referred to here is the thickness of the dried film.

[0031] <Positive photosensitive resist layer (C)> The positive photosensitive resist layer (C) contains a resol-modified xylene formaldehyde resin (b) containing at least a structural unit (I) represented by the following general formula (1) and a structural unit (II) represented by the following general formula (2), and also contains a quinone diazide sulfonate (c) which is a polycondensate of a sulfonate ester of phenol formaldehyde and o-naphthoquinone diazide, or a polycondensate of a sulfonate ester of an alkylphenol formaldehyde and o-naphthoquinone diazide.

[0032] [ka]

[0033] [ka] (In general formulas (1) and (2), X each independently represents -CH2- or -CH2-O-CH2-, and in general formula (2), m represents an integer of 1 to 2, and when the resin (b) contains a plurality of structural units (II), m in each structural unit (II) may be the same or different.)

[0034] (Resol-modified xylene formaldehyde resin (b)) The constituent unit (I) in the resol-modified xylene formaldehyde resin (b) (hereinafter also referred to as resin (b)) is a constituent unit derived from m-xylene. The constituent unit (II) is a constituent unit derived from phenol. Such resin (b) can be obtained by copolymerization of m-xylene, phenol and formaldehyde using a basic catalyst. Therefore, resin (b) is preferably a copolymer resol resin of these. Resin (b) is also a polymer composition in which the constituent units (I) and (II) are crosslinked by methylene bonds or ether bonds.

[0035] The molar ratio of the structural unit (I) to the structural unit (II) in the resin (b) is preferably structural unit (I):structural unit (II)=1:4 to 2:1.

[0036] The resin (b) may have a structural unit as shown in the following formula (3) at its molecular terminal. [ka]

[0037] The number average molecular weight of the resin (b) is preferably 1400 or less, and more preferably 1100 or less. In addition, the number average molecular weight is preferably 500 or more. It is preferable that the number average molecular weight of resin (b) is 1,400 or less, since the softening point of resin (b) is low and good adhesion can be obtained between the substrate and the positive photosensitive resist layer during thermal lamination.

[0038] The number average molecular weight of the resin (b) can be measured, for example, by gel permeation chromatography using the following apparatus and conditions. Equipment: Shodex (registered trademark) GPC-101 type (Resonac Corporation product) Column: KF-80M x 3 Eluent: THF 1ml / min Temperature: 40℃ Standard material: polystyrene

[0039] ((c) Quinone diazide sulfonic acid esters) In the present invention, the quinone diazide sulfonic acid ester contained in the positive photosensitive resist is a polycondensate of a sulfonic acid ester of phenol formaldehyde and o-naphthoquinone diazide, or a polycondensate of a sulfonic acid ester of an alkylphenol formaldehyde and o-naphthoquinone diazide (hereinafter, these are also referred to as ester (c)). The number of carbon atoms in the alkyl group of such alkylphenol formaldehyde is preferably 3 or less, more preferably 1 or less. Specific examples of such polycondensates include o-naphthoquinone diazide sulfonic acid esters of polycondensates of p-cresol and formaldehyde, o-naphthoquinone diazide sulfonic acid esters of polycondensates of o-cresol and formaldehyde, o-naphthoquinone diazide sulfonic acid esters of polycondensates of m-cresol and formaldehyde, and o-naphthoquinone diazide sulfonic acid esters of polycondensates of phenol and formaldehyde. In the ester (c), the quinone diazide groups are linearly arranged in the molecule, so that the proportion of quinone diazide groups accessible to the phenolic hydroxyl groups of the resin (b) is higher than that of other quinone diazide sulfonic acid esters, and the effect of inhibiting dissolution of the unexposed resist pattern in the developer is more potent. The quinone diazide sulfonate preferably used in the present invention includes 1,2-naphthoquinone diazide-5-sulfonate, which is a polycondensate of p-cresol and formaldehyde (for example, MIPHOTO PAC100K (trade name, Miwon Commercial Co., Ltd.)).

[0040] When the positive photosensitive resist layer (C) contains the above resin (b) and the above ester (c), it is possible to obtain a positive dry film resist that has excellent lamination properties to a substrate and that is improved in the reduction of resist pattern reproducibility due to the reduction in the top width of the resist pattern caused by the elution of the unexposed parts by the developer when the photosensitive resist layer is exposed and developed to form a pattern. In particular, when the resin (b) contains a resol-modified xylene formaldehyde resin, the above-mentioned effects are more pronounced, which is preferable.

[0041] The positive photosensitive resist layer (C) may further contain an alkali-soluble novolak resin (d).

[0042] The alkali-soluble novolak resin (d) (hereinafter also referred to as resin (d)) is a resin obtained by condensing a phenol or naphthol with an aldehyde or ketone using an acid catalyst. The term "phenol" as used herein includes cresols, xylenols, resorcinols, catechols, pyrogallols, and other "all compounds in which a phenolic hydroxyl group is bonded to an aromatic ring such as a benzene ring." Examples of the alkali-soluble novolak resin (d) include phenol novolak resin, cresol novolak resin, xylenol novolak resin, resorcinol novolak resin, and naphthol novolak resin.

[0043] Examples of phenols or naphthols that can be used as raw materials for the alkali-soluble novolak resin (d) include phenol, o-cresol, m-cresol, p-cresol, o-ethylphenol, m-ethylphenol, p-ethylphenol, o-propylphenol, m-propylphenol, p-propylphenol, o-butylphenol, m-butylphenol, p-butylphenol, octylphenol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, 3,5-xylenol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, 3,5-xylenol, 2,5-xylenol, 2,6-xylenol, 2,4 ...5-xylenol, 2,6-xylenol, 2,4-xylenol, 2,5-xylenol, 2,5-xylenol, 2,5-xylenol, 2,6 , 3,5-trimethylphenol, 3,4,5-trimethylphenol, methoxyphenol, 2-methoxy-4-methylphenol, vinylphenol, allylphenol, benzylphenol, methoxycarbonylphenol, benzoyloxyphenol, chlorophenol, catechol, resorcinol, pyrogallol, bisphenol A, bisphenol F, β-naphthol, p-hydroxyphenyl-2-ethanol, p-hydroxyphenyl-3-propanol, p-hydroxyphenyl-4-butanol, hydroxyethylcresol, etc. These phenols can be used alone or in combination of two or more kinds.

[0044] Examples of the aldehydes or ketones used to obtain the alkali-soluble novolak resin (d) include formaldehyde, acetaldehyde, propylaldehyde, butylaldehyde, isobutylaldehyde, furfural, benzaldehyde, hydroxybenzaldehyde, methoxybenzaldehyde, hydroxyphenylacetaldehyde, methoxyphenylacetaldehyde, crotonaldehyde, chloroacetaldehyde, chlorophenylacetaldehyde, acetone, glyceraldehyde, glyoxylic acid, methyl glyoxylate, phenyl glyoxylate, hydroxyphenyl glyoxylate, formylacetic acid, and methyl formylacetate. These aldehydes or ketones can be used alone or in combination of two or more. Condensates of these can also be used.

[0045] The alkali-soluble novolak resin (d) is preferably a co-condensed novolak resin made of p-cresol, m-cresol, and aldehydes or ketones, and the amount of p-cresol is preferably 55 mol% or more based on the total amount of p-cresol and m-cresol used in the co-condensation. Here, the term "co-condensed novolak resin made of p-cresol, m-cresol, and aldehydes or ketones" means that the total amount of p-cresol and m-cresol is 50 to 100 mol% based on the total amount of phenols or naphthols that are the raw materials for the novolak resin.

[0046] In the above-mentioned copolymer novolak resin, the total of p-cresol and m-cresol is more preferably 60 to 100 mol%, further preferably 70 to 100 mol%, even more preferably 80 to 100 mol%, still more preferably 90 to 100 mol%, particularly preferably 96 to 100 mol%, and may be 100 mol%. When the total of p-cresol and m-cresol is less than 100 mol% of the total of phenols or naphthols, the remaining components are not particularly limited, and include the above-mentioned "phenols or naphthols" excluding p-cresol and m-cresol.

[0047] In addition, the formaldehyde or the formaldehyde condensate is preferably contained in an amount of 50 to 100 mol%, more preferably 60 to 100 mol%, even more preferably 70 to 100 mol%, still more preferably 80 to 100 mol%, even more preferably 90 to 100 mol%, and particularly preferably 96 to 100 mol% based on the total amount of phenols or naphthols. When the formaldehyde or the formaldehyde condensate is less than 100 mol%, the remaining components are not particularly limited, and include the above-mentioned "aldehydes or ketones" excluding formaldehyde and the formaldehyde condensate.

[0048] The co-condensed novolak resin composed of p-cresol, m-cresol, and aldehydes or ketones is preferably such that the amount of p-cresol relative to the total amount of p-cresol and m-cresol used in the co-condensation is 55 mol% or more, which makes it easier for the molecules to grow linearly during the co-condensation reaction, and suppresses crosslinking in the three-dimensional direction, thereby suppressing the weight average molecular weight (Mw) of the obtained co-condensed novolak resin to 6,000 or less. This reduction in molecular weight can achieve a decrease in Tg of the co-condensed novolak resin and an improvement in flexibility, making it difficult for poor adhesion to the substrate to occur when thermocompression bonding is performed by a lamination method. In addition, an increase in the proportion of p-cresol increases the dissolution rate of the exposed portion of the positive photosensitive resist layer (C), and reduces the contact time of the unexposed portion with the developer, making it difficult for a decrease in the top width of the resist pattern or chipping of the resist pattern to occur due to dissolution of the unexposed portion by the developer. The amount of p-cresol based on the total amount of p-cresol and m-cresol used in the co-condensation is more preferably 60 mol % or more.

[0049] The positive photosensitive resist layer (C) may or may not contain a phenol aralkyl resin (e). The phenol aralkyl resin (e) (hereinafter also referred to as resin (e)) is a reaction product of an aralkyl compound and a phenol compound using an acid catalyst. Examples of the phenol aralkyl resin (e) include novolak-type xylene resin modified with a phenol resin (e.g., GP-100 6M22 (trade name, Fudow Corporation)), xylene resin modified with an alkylphenol resin (e.g., Nikanol (registered trademark) HP-70 (trade name, Fudow Corporation)), and copolymers of 4,4-bis(methoxymethyl)biphenyl and phenol (e.g., KAYAHARD (registered trademark) GPH-65 (trade name, Nippon Kayaku Co., Ltd.)).

[0050] The preferred ratio of each component to the total solid content contained in the positive photosensitive resist layer (C) is as follows: In this specification, the solid content contained in the positive photosensitive resist layer (C) means the total solid content of the resin (b), the quinone diazide sulfonic acid ester, the resin (d) and the resin (e), and does not include residual solvent components.

[0051] The proportion of the resin (b) in the total solid content contained in the positive photosensitive resist layer (C) is preferably from 35 to 90 mass %, and more preferably from 40 to 85 mass %. It is more preferable that the proportion of resin (b) is 40% by mass or more in order to lower the softening point of the film and improve the possible thermocompression bonding speed, and it is more preferable that the proportion of resin (b) is 85% by mass or less in order to maintain good film-forming properties of the resist film.

[0052] The proportion of the ester (c) in the solid content contained in the positive photosensitive resist layer (C) is preferably from 8 to 35 mass %, and more preferably from 9 to 30 mass %. When the proportion of the ester (c) is from 9 to 30% by mass, it is more preferable from the viewpoint of obtaining a dry film resist that has particularly excellent lamination properties with respect to the substrate surface.

[0053] When the positive photosensitive resist layer (C) contains the resin (d), the proportion of the resin (d) in the solid content contained in the positive photosensitive resist layer (C) is preferably 35 mass % or less. If the proportion of the resin (d) is 35 mass % or less, it is preferable from the viewpoint of lowering the softening point of the film and improving the possible speed of thermocompression bonding. The positive photosensitive resist layer (C) may not contain the resin (d).

[0054] When the positive photosensitive resist layer (C) contains a phenol aralkyl resin (e), the proportion of the phenol aralkyl resin (e) in the solid content contained in the positive photosensitive resist layer (C) is preferably 3.0 mass% or less. Also, the positive photosensitive resist layer (C) preferably does not contain a phenol aralkyl resin (e). When the positive photosensitive resist layer (C) contains a large amount of the phenol aralkyl resin (e), the reproducibility of the resist pattern may decrease, or the compatibility with other components may decrease.

[0055] The positive photosensitive resist layer (C) may contain a solvent component. Examples of the solvent component include organic solvents. The solvent component is not particularly limited as long as it has sufficient solubility for each component contained in the positive photosensitive resist layer (C) and has good coatability. Examples of such solvent components include aromatic solvents such as xylene, cellosolve-based solvents such as methyl cellosolve, ethyl cellosolve, methyl cellosolve acetate, and ethyl cellosolve acetate, propylene glycol-based solvents such as propylene glycol and dipropylene glycol, propylene glycol alkyl ether-based solvents such as propylene glycol monomethyl ether and propylene glycol monobutyl ether, propylene glycol alkyl ether acetate-based solvents such as propylene glycol monomethyl ether acetate, propylene glycol dimethyl ether, and propylene glycol monoethyl ether acetate, butyl acetate, pentyl acetate, methyl lactate, lactic acid, and the like. Examples of the solvent include ester solvents such as ethyl ether, 3-methoxypropionic acid, ethyl 3-ethoxypropionate, and γ-butyrolactone; alcohol solvents such as methanol, ethanol, isopropyl alcohol, butanol, hexanol, and diacetone alcohol; ketone solvents such as acetone, cyclohexanone, cyclopentanone, methyl ethyl ketone, methyl pentyl ketone, and methyl isobutyl ketone; ether solvents such as methyl phenyl ether and diethylene glycol dimethyl ether; cyclic ether solvents such as dioxane and dioxolane; highly polar solvents such as N,N-dimethylformamide, N-methylpyrrolidone, and dimethyl sulfoxide; and mixed solvents thereof. These may be used alone or in combination of two or more.

[0056] The content of the solvent component is preferably 3% by mass or more and 10% by mass or less, more preferably 4% by mass or more and 8% by mass or less, and even more preferably 5% by mass or more and 7% by mass or less, based on the total solid content of the positive photosensitive resist layer (C). If the content of the solvent component is less than 3% by mass, the dissolution rate of the exposed portion of the positive photosensitive resist layer (C) in the developer decreases, and it may be difficult to form a resist pattern. If the content of the solvent component is more than 10% by mass, the dissolution rate of both the exposed portion and the unexposed portion in the developer becomes too high, and the surface of the unexposed portion dissolves during the development process, which may easily cause chipping of the resist pattern or unevenness of the image line. In addition, the film thickness of the unexposed portion may be reduced.

[0057] The content of the solvent component in the positive photosensitive resist layer (C) is calculated by the following method. A dry film resist in which a peeling layer (B) and a positive photosensitive resist layer (C) are formed in this order on a support film (A) is attached by thermocompression bonding using a lamination method so that the positive photosensitive resist layer (C) contacts the copper foil, and the support film (A) and the peeling layer (B) are removed from the positive photosensitive resist layer (C), and then a sample of 10 cm square is cut out. The mass W1 of the sample is measured, and then the sample is dried in a dryer at 130°C for 15 minutes. The mass W2 of the sample returned to room temperature after drying is measured, and the mass loss W1-W2 is taken as the mass W3 of the solvent component contained in the positive photosensitive resist layer (C). Then, the positive photosensitive resist layer (C) is dissolved in methyl ethyl ketone and removed from the copper foil, and the mass W4 of the copper foil dried at 80°C for 5 minutes is measured. The value W1-W4 obtained by subtracting the mass W4 of the copper foil from the mass W1 is defined as the mass (total) W5 of the positive photosensitive resist layer (C) including the solvent component. The ratio of mass W3 to mass W5 (W3 / W5×100) is calculated as the content of the solvent component in the positive photosensitive resist layer (C).

[0058] The positive photosensitive resist layer (C) may contain other components. Examples of the other components include polypropylene glycol glyceryl ether, carboxyl group-containing poly(meth)acrylate, polyurethane, vinyl acetate resin, polyamide, and other resins. The incorporation of "other components" such as these resins may improve flexibility, etching solution resistance, developability, and adhesion. The positive photosensitive resist layer (C) may also contain additives such as colorants (dyes, pigments), photocoloring agents, photocolor-reducing agents, thermal color-developing inhibitors, fillers, defoamers, flame retardants, adhesion-imparting agents, leveling agents, peeling promoters, antioxidants, fragrances, heat curing agents, water repellents, and oil repellents.

[0059] The above-mentioned "other components" and "additives" can each be contained in an amount of about 0.01 to 20 mass % based on the total amount of the positive photosensitive resist layer (C). These components can be used alone or in combination of two or more.

[0060] The thickness of the positive photosensitive resist layer (C) is preferably 1 to 20 μm, more preferably 2 to 10 μm. If it is less than 1 μm, air bubbles may easily be trapped during thermocompression bonding to a substrate. Furthermore, problems of thickness unevenness and pinholes may easily occur when a film is formed. On the other hand, if it is thicker than 20 μm, the light may not reach the bottom of the positive photosensitive resist layer (C) during exposure, and the bottom of the resist pattern may become thick and trapezoidal, making it impossible to form a thin line. The thickness of the positive photosensitive resist layer (C) is the thickness after drying.

[0061] Examples of a method for forming a release layer (B) on a support film (A) and a method for providing a positive photosensitive resist layer (C) on the release layer (B) include coating methods using a roll coater, a comma coater (registered trademark), a gravure coater, an air knife, a die coater, a bar coater, etc.

[0062] <Protective film (D)> In the positive dry film resist of the present invention, the positive photosensitive resist layer (C) may be covered with a protective film (D) as necessary. The protective film (D) is provided to prevent blocking of the positive photosensitive resist layer (C) to the support film (A) when the positive dry film resist is rolled up, and is provided on the positive photosensitive resist layer (C) on the side opposite to the support film (A) and the peeling layer (B). The protective film (D) is preferably one with small fish eyes. Examples of the protective film include polyvinyl chloride film, polyethylene film, polypropylene film, and polyester film.

[0063] It is preferable to use a self-adhesive resin film as the protective film (D). The self-adhesive resin film is a film formed by co-extrusion of a base layer and an adhesive layer. Such a self-adhesive resin film is preferable because there is little concern about contamination of the product due to outgassing components, adhesive residue, component migration, etc. In addition, the positive photosensitive resist layer (C) can be covered with the protective film (D) without heating.

[0064] The self-adhesive resin film is composed of at least a base layer and an adhesive layer, the base layer does not have self-adhesiveness, and examples of the material include those mentioned above. In addition, it is preferable to use an adhesive layer that can be attached to a PMMA (polymethyl methacrylate) plate at 23°C and has an adhesive strength of 0.01 N / 50 mm width or more and 0.30 N / 50 mm width or less. Examples of the adhesive layer include ethylene vinyl acetate copolymer; polyolefins such as polyethylene and polypropylene; polyamide; synthetic rubber; polyacrylate; polyurethane; and the like. The material of the adhesive layer is designed to have self-adhesive properties by adjusting the molecular weight or adding a plasticizer. Examples of commercially available adhesives include Toretec (registered trademark, manufactured by Toray Film Processing Co., Ltd.), FSA (registered trademark, manufactured by Futamura Chemical Co., Ltd.), and Sanitect (registered trademark, manufactured by San-A Kaken Co., Ltd.).

[0065] The thickness of the protective film (D) is preferably 5 to 100 μm. If the thickness of the protective film (D) is less than 5 μm, handling may be difficult, and if it is more than 100 μm, the cost may be high, and the roll may become bulky and heavy.

[0066] <Etching method> Next, the etching method using the positive dry film resist of the present invention will be described in detail. First, it is preferable to attach the positive dry film resist of the present invention to at least one side of a substrate by thermocompression bonding using a lamination method so that the positive photosensitive resist layer (C) contacts the substrate. When the positive dry film resist of the present invention has a protective film (D), it is preferable to attach the positive photosensitive resist layer (C) to at least one side of the substrate after peeling off the protective film (D) so that the positive photosensitive resist layer (C) contacts the substrate.

[0067] The substrate according to the present invention is a substrate on which etching is performed, and is determined by the product. In the manufacture of printed wiring boards, lead frames, metal masks, shadow masks, semiconductor packages, electrode members, electromagnetic shields, etc., a substrate containing a metal is selected. For example, "substrates containing a metal (i.e., metal substrates)" such as copper, copper-based alloys (titanium-copper alloys, copper-nickel alloys, etc.), nickel, chromium, iron, tungsten, stainless steel, iron-based alloys such as 42 alloy, aluminum, amorphous alloys, etc. can be used. In addition, metal oxide films such as ITO and FTO can be used as the substrate. Furthermore, copper-clad laminates, (non-)electrolytically plated substrates, flexible copper-clad laminates, flexible stainless steel plates, laminates, etc., which are used in the manufacture of printed wiring boards, can be used as the substrate.

[0068] The method of attaching the positive dry film resist of the present invention to at least one side of the substrate is preferably a lamination method. A general thermal laminator for printed circuit boards or a vacuum laminator can be used for such attachment. The nip pressure, conveying speed, and roll temperature vary depending on the substrate used, but any conditions are acceptable as long as the attachment can be achieved by thermocompression bonding without bubbles or unevenness.

[0069] After the positive dry film resist is applied to the substrate, the support film (A) or the support film (A) having the release layer (B) is removed from the positive photosensitive resist layer (C). In the latter case, it is preferable to remove the support film (A) and the release layer (B) simultaneously. In the latter case, the embodiment in which only the support film (A) is removed is not excluded, and even in this case, the remaining release layer (B) can be easily removed by a developer when the resist pattern is formed by subsequent development.

[0070] Next, the positive photosensitive resist layer (C) is exposed to a desired pattern. It is preferable to use ultraviolet light for exposure. The exposure method is performed by laser direct drawing, contact exposure through a photomask, projection exposure, etc. As a light source for exposure, an ultra-high pressure mercury lamp, a high pressure mercury lamp, a metal halide lamp, a xenon lamp, a laser, an LED, etc. can be used.

[0071] Next, development is carried out. The exposed portion of the positive photosensitive resist layer (C) is removed by development. An alkaline aqueous solution is useful as a developer used for development. Examples of basic compounds used in the developer include inorganic basic compounds such as alkali metal silicate, alkali metal hydroxide, alkali metal phosphate, alkali metal carbonate, ammonium phosphate, and ammonium carbonate; and organic basic compounds such as ethanolamine, ethylenediamine, propanediamine, triethylenetetramine, morpholine, and tetramethylammonium hydroxide.

[0072] In order to adjust the developability of the exposed portion of the positive photosensitive resist layer (C), it is desirable to adjust the concentration, temperature, spray pressure, etc. of the developer. The temperature of the developer is preferably 20 to 40°C, more preferably 25 to 35°C. The concentration of the basic compound in the developer is preferably 0.3 to 3.0% by mass in the case of potassium hydroxide. As the device, a dip treatment device, a shower spray device, or the like can be used.

[0073] Next, the substrate is etched. In the present invention, any etching solution, device, or method may be used as long as it can dissolve and remove the substrate used. Examples of the etching solution include alkaline ammonia solution, sulfuric acid-hydrogen peroxide solution, cupric chloride solution, persulfate solution, ferric chloride solution, aqua regia, and the like. Examples of the device or method that can be used include horizontal spray etching, immersion etching, and the like. Details of these are described in "Printed Circuit Technology Handbook" (edited by the Japan Printed Circuit Association, published in 1987, and published by the Nikkan Kogyo Shimbun, Ltd.).

[0074] Next, the resist is stripped using a stripping solution, but before that, the resist pattern may be exposed to ultraviolet light. By exposure, the positive photosensitive resist layer (C) becomes easier to remove using the stripping solution. As the stripping solution, a strong alkaline aqueous solution is usefully used. Examples of basic compounds contained in the stripping solution include inorganic basic compounds such as alkali metal silicate, alkali metal hydroxide, alkali metal phosphate, alkali metal carbonate, ammonium phosphate, and ammonium carbonate; organic basic compounds such as ethanolamine, ethylenediamine, propanediamine, triethylenetetramine, morpholine, and tetramethylammonium hydroxide; and the like.

[0075] In the resist stripping step, it is preferable to adjust the concentration, temperature, spray pressure, ultrasonic conditions, etc. of the stripping solution. The higher the temperature of the stripping solution, the faster the rate at which the positive photosensitive resist layer (C) dissolves, and a temperature of 40°C or higher is preferable. The concentration of the basic compound in the stripping solution is preferably a concentration suitable for solubility, and when the basic compound is sodium hydroxide or potassium hydroxide, it is preferably 1 to 4 mass%. As the device used for resist stripping, a dip treatment device, an ultrasonic device, a shower spray device, etc. can be used.

[0076] The present specification discloses the following:

[0077] The present disclosure (1) is a dry film resist comprising: a support film (A); and a positive photosensitive resist layer (C) on the support film (A), the positive photosensitive resist layer (C) containing a resol-modified xylene formaldehyde resin (b) containing at least a structural unit (I) represented by the following general formula (1) and a structural unit (II) represented by the following general formula (2), and a quinone diazide sulfonic acid ester (c), the quinone diazide sulfonic acid ester (c) being a polycondensate of a sulfonic acid ester of phenol formaldehyde and o-naphthoquinone diazide, or a polycondensate of a sulfonic acid ester of an alkylphenol formaldehyde and o-naphthoquinone diazide. It is.

[0078] [ka]

[0079] [ka] (In general formulas (1) and (2), X each independently represents -CH2- or -CH2-O-CH2-, and in general formula (2), m represents an integer of 1 to 2, and when the resin (b) contains a plurality of structural units (II), m in each structural unit (II) may be the same or different.) EXAMPLES

[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0081] Polyvinyl alcohol (trade name: Kuraray Poval (registered trademark) 44-88 (saponification degree 87-89 mol%, Kuraray Co., Ltd.) was prepared, and 80 parts by mass of water was added to 5 parts by mass of polyvinyl alcohol, and the polyvinyl alcohol was dissolved by stirring with warm water to obtain an aqueous polyvinyl alcohol solution. Next, 15 parts by mass of ethanol was added to prepare a coating liquid for a release layer with a solid content of 5% by mass. The coating liquid for a release layer was applied to one side of a polyethylene terephthalate (PET) film (support film (A), trade name: Diafoil (registered trademark) T100, 25 μm thick, manufactured by Mitsubishi Chemical Corporation) using a wire bar. Thereafter, the coating liquid for a release layer was dried at 90° C. for 15 minutes, and a release layer containing polyvinyl alcohol was provided on the support film (A) to a thickness of 2 μm, to obtain a laminated film having a support film (A) and a release layer (B).

[0082] Each component (parts by weight) having the composition shown in each of the examples and comparative examples in Table 1 was dissolved in 300 parts by weight of propylene glycol monomethyl ether acetate, and the solution was filtered through a membrane filter (pore size 1 μm) to obtain a coating liquid for a positive photosensitive resist layer.

[0083] The coating liquid for the positive photosensitive resist layer was applied to the peeling layer surface of the laminated film using a wire bar. After that, it was dried at 90°C for 10 minutes, and a positive photosensitive resist layer was provided on the peeling layer with a thickness of 6 μm, to prepare a positive dry film resist having a three-layer structure (support film (A) / peeling layer (B) / positive photosensitive resist layer (C)). The positive photosensitive resist layer after drying contains 5% by mass of a solvent component.

[0084] The components listed in Table 1 are as follows. Table 1 shows the amount of each component blended in terms of solid content (amount of active ingredient / part by mass). (b) Resol-modified xylene formaldehyde resin (b-1) Nikanol (registered trademark) PR-1440M (product name, Fudow Co., Ltd., resol-modified xylene formaldehyde resin, number average molecular weight 911, molar ratio of structural unit (I) to structural unit (II) is approximately 1:1), a compound having a representative structure in which m in general formula (2) is 1 to 2. 45% dilution with methanol.

[0085] (c) Polycondensation products of phenol formaldehyde and sulfonic acid ester of o-naphthoquinone diazide, or polycondensation products of alkylphenol formaldehyde and sulfonic acid ester of o-naphthoquinone diazide (c-1) 1,2-naphthoquinone diazide-5-sulfonic acid ester of p-cresol and formaldehyde polycondensate (c-2) 1,2-naphthoquinonediazide-4-sulfonic acid ester of p-cresol and formaldehyde polycondensate

[0086] (d) Alkali-soluble novolak resin (d-1) Novolak resin EP6050G (manufactured by Asahi Organic Chemicals Co., Ltd., weight average molecular weight 2,500 to 4,000, the amount of p-cresol relative to the total amount of p-cresol and m-cresol used in co-condensation is 60 mol%)

[0087] (c") Quinone diazide sulfonic acid esters other than ester (c) (c"-1) o-Naphthoquinonediazidesulfonic acid ester of 2,3,4-trihydroxybenzophenone (c"-2) o-Naphthoquinonediazidesulfonic acid ester of 4,4'-(1-{4-[2-(4-hydroxyphenyl)propan-2-yl]phenyl}ethane-1,1-diyl)diphenol

[0088] [Table 1]

[0089] (Lamination properties) The following tests were carried out 1 hour after the coating liquid of Examples 1 to 7 and Comparative Examples 1 to 3 was applied and dried to provide a positive photosensitive resist layer on the release layer. The positive dry film resist of Examples 1 to 7 and Comparative Examples 1 to 3 was attached to the copper layer surface of a polished and degreased copper-clad laminate by thermocompression bonding using a lamination method so that the positive photosensitive resist layer of the positive dry film resist of Examples 1 to 7 and Comparative Examples 1 to 3 was in contact with the copper layer surface. A general printed circuit board laminator was used for this purpose. The lamination conditions were a roll temperature of 100°C, a pressure of 0.4 MPa, and a conveying speed of 0.5 m / min, 0.6 m / min, and 0.8 m / min.

[0090] After the copper-clad laminate with the positive dry film resist attached thereto was returned to room temperature (25°C), the support film and the release layer were peeled off, and the state in which the positive photosensitive resist layer was attached to the surface of the copper layer without any defects was deemed to be lamination-possible. When the support film and the release layer were peeled off, the state in which a part or all of the positive photosensitive resist layer on the surface of the copper layer was transferred onto the release layer due to insufficient adhesion between the positive photosensitive resist layer and the copper-clad laminate was deemed to be lamination-possible. The test results in each example and comparative example were as follows: × if lamination was not possible at a conveying speed of 0.5 m / min; △ if lamination was possible at a conveying speed of more than 0.5 m / min and not possible at a conveying speed of 0.6 m / min; ◯△ if lamination was possible at a conveying speed of more than 0.6 m / min and not possible at a conveying speed of 0.8 m / min; and ◯ if lamination was possible at a conveying speed of more than 0.8 m / min.

[0091] As a result, the lamination property was particularly good in Examples 1 to 5. Examples 6 and 7 are examples in which the ratio of the polycondensate of sulfonic acid ester of phenol formaldehyde and o-naphthoquinone diazide, or the polycondensate of sulfonic acid ester of alkylphenol formaldehyde and o-naphthoquinone diazide (c) is slightly higher or lower, and the lamination property was slightly inferior to that of Examples 1 to 5, but was practically sufficient. Comparative Example 3 did not use the resol-modified xylene formaldehyde resin (b), and therefore lamination was not possible.

[0092] (Resist pattern reproducibility) Using an ultra-high pressure mercury lamp ultraviolet irradiation device, a test chart mask having 10 μm lines and spaces was placed on the positive photosensitive resist layer of Examples 1 to 7 and Comparative Examples 1 to 2 attached to a copper-clad laminate, and exposed by suction. Next, the positive photosensitive resist layer of Examples 1 to 7 and Comparative Example 2 was immersed in a 1.5 mass% potassium hydroxide aqueous solution (developer, 30° C.) for the positive photosensitive resist layer of Examples 1 to 7 and Comparative Example 2, and in a 0.8 mass% potassium hydroxide aqueous solution (developer, 30° C.) for the positive photosensitive resist layer of Comparative Example 1 for 50 seconds, and the positive photosensitive resist layer of the exposed area was removed and development was performed (the concentration of the potassium hydroxide aqueous solution was changed and development was performed so that the reduction in the top width near the apex of the obtained resist pattern was adjusted as small as possible). Then, it was washed with water and dried.

[0093] The shapes of the 10 μm wide lines and spaces of the resist patterns of Examples 1 to 7 and Comparative Examples 1 and 2 were confirmed by observation. For the line patterns of each width, if there was no residue in the space portion and the difference between the top width and the bottom width due to film reduction was within 1.2 μm, the resist pattern shape was judged to be good (evaluated as ◯), and if the difference between the top width and the bottom width exceeded 1.2 μm, the resist pattern shape was judged to be poor (evaluated as ×).

[0094] As a result, the resist pattern shapes were good in all of Examples 1 to 7. Comparative Examples 1 and 2 are examples in which a polycondensate of a sulfonic acid ester of phenol formaldehyde and o-naphthoquinone diazide, or a quinone diazide sulfonic acid ester (c), which is a polycondensate of a sulfonic acid ester of alkylphenol formaldehyde and o-naphthoquinone diazide, was not used, and the resist pattern shapes were poor in all of them. [Industrial Applicability]

[0095] The positive dry film resist of the present invention can be used in the production of metal masks, lead frames, shadow masks, printed circuit boards, and the like.

Claims

[Claim 1] A dry film resist comprising: a support film (A); and a positive photosensitive resist layer (C) on the support film (A), the positive photosensitive resist layer (C) containing a resol-modified xylene formaldehyde resin (b) containing at least a structural unit (I) represented by the following general formula (1) and a structural unit (II) represented by the following general formula (2), and a quinone diazide sulfonic acid ester (c), the quinone diazide sulfonic acid ester (c) being a polycondensate of a sulfonic acid ester of phenol formaldehyde and o-naphthoquinone diazide, or a polycondensate of a sulfonic acid ester of an alkylphenol formaldehyde and o-naphthoquinone diazide. 【Chemistry 1】 【Chemistry 2】 In the general formulas (1) and (2), each X is independently -CH 2 -or-CH 2 -O-CH 2 In the general formula (2), m represents an integer of 1 to 2, and when the resin (b) contains a plurality of structural units (II), m in each structural unit (II) may be the same or different.

Citation Information

Patent Citations

  • Laminated sheet of positive photosensitive resin and method for manufacturing the same

    JP2006267660A

  • Photosensitive resin composition and photosensitive resin laminate including the same

    JP2020098241A

  • Photosensitive resin composition

    JP2020098242A

  • Photosensitive resin laminate and resist pattern manufacturing method

    JP2020098244A

  • Dry film resist

    JP2024175491A